Differences in the Effectiveness of Audiovisual Media and Leaflets on the Knowledgeand Attitudes of Mothers of Toddlers in Bogorejo Village About Stunting - Caesar Erza Keryn Febriyanti; Noor Alis Setiyadi (P3M Universitas 'Aisyiyah Surakarta, 2023)
One of the factors causing children to suffer from stunting is inappropriate parenting due to the lack of maternal knowledge about stunting and the fulfillment of toddler nutrition. Knowledge affects attitudes and behavior. The way to increase maternal knowledge and attitudes can be done by providing health education using media such as leaflets and audiovisuals. This study aims to determine which media are effective in increasing the knowledge and attitudes of mothers of toddlers regarding stunting. This type of research is Quasi Experiment One Group Pre-Test Post-Test With Control Group.The sample size was 95 respondents and divided into three groups. Questionnaires were used as a data collection tool. The three groups were compared using One Way Anova statistics followed by Tukey test at the 0,05 level of significance. There was a significant difference in the knowledge and attitude of the leaflet and audiovisual groups (p = 0,001) and there was no significant difference in the control group (p = 0,980) after being given health education. Leaflet and audiovisual media are effective for improving the knowledge and attitudes of mothers of toddlers about stunting.